2015
DOI: 10.15653/tpg-140905
|View full text |Cite
|
Sign up to set email alerts
|

Histopathologic lesions in conventional pigs experimentally infected with Haemophilus parasuis serovar 5

Abstract: H. parasuis constantly causes clinical signs and pathologic lesions as soon as it infects the brain while it can infect the joints without causing histopathologic lesions. Pigs with histopathologic lesions do not always show typical clinical signs. Only few studies described the finding of kidney lesions in pigs with Glässer's disease and this is the first study to describe a pyelitis in pigs experimentally infected with H. parasuis. The observed pyelitis mainly occurred in acute cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 13 publications
1
0
0
Order By: Relevance
“…We confirmed a strong inflammatory response characterized by high expression of inflammatory cytokines in skeletal muscle due to G. parasuis infection. This finding aligns with the well-known predilection sites of G. parasuis infection, such as the lung, arthrosis, pleura, peritoneum, kidney, and meninges [ 42 , 43 , 44 ]. It has been reported that G. parasuis breaks through the lung’s immune defense [ 45 ], allowing it to colonize various parts of the body, including skeletal muscle, through the bloodstream.…”
Section: Discussionsupporting
confidence: 87%
“…We confirmed a strong inflammatory response characterized by high expression of inflammatory cytokines in skeletal muscle due to G. parasuis infection. This finding aligns with the well-known predilection sites of G. parasuis infection, such as the lung, arthrosis, pleura, peritoneum, kidney, and meninges [ 42 , 43 , 44 ]. It has been reported that G. parasuis breaks through the lung’s immune defense [ 45 ], allowing it to colonize various parts of the body, including skeletal muscle, through the bloodstream.…”
Section: Discussionsupporting
confidence: 87%